2017
DOI: 10.1108/ecam-06-2015-0103
|View full text |Cite
|
Sign up to set email alerts
|

Predicting likelihood of cost overrun in educational projects

Abstract: Purpose Being able to predict the likelihood of a project to overrun its cost before the contract signing phase is crucial in developing the required mitigating measures to avert it. Known parameters that permit the timely prediction of cost overrun provide the basis for such predictions. Therefore, the purpose of this paper is to develop a model for forecasting cost overruns. Design/methodology/approach Ten predictive variables known before the contract signing phase of a project are identified. Based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…A MAPE of 26 per cent at the validation stage is also consistent with Wang et al (2000) and Bode (1998) with a deviation of 24.5 and 24 per cent, respectively. According to Asiedu et al (2016), an MAPE of 26 per cent can be regarded as good and is much better than the MAPE values of 138 and 60.7 per cent obtained by the studies conducted by Asiedu et al (2017) and Asiedu et al (2016), respectively. Model 2 is eventually selected with a good predictive ability at the validation stage (coefficient of determination, R 2 = 88.5 per cent).…”
Section: Artificial Neural Network Model Developmentmentioning
confidence: 63%
See 1 more Smart Citation
“…A MAPE of 26 per cent at the validation stage is also consistent with Wang et al (2000) and Bode (1998) with a deviation of 24.5 and 24 per cent, respectively. According to Asiedu et al (2016), an MAPE of 26 per cent can be regarded as good and is much better than the MAPE values of 138 and 60.7 per cent obtained by the studies conducted by Asiedu et al (2017) and Asiedu et al (2016), respectively. Model 2 is eventually selected with a good predictive ability at the validation stage (coefficient of determination, R 2 = 88.5 per cent).…”
Section: Artificial Neural Network Model Developmentmentioning
confidence: 63%
“…According to Stoy et al (2007); the positive coefficients of IC, SB and H could indicate that massive or large projects enable efficient use of production factors which in effect would result in speed of construction than in smaller projects, thereby shortening the duration of the entire bridge construction project. The shortening of duration can be attributed to the principle of economy of scale, where larger projects tend to be well planned and better managed than smaller projects because the stakes are often high (Asiedu et al, 2017). This could possibly be the reason for the negative coefficient of BW in equation ( 6).…”
Section: Discussion Of Mlr and Ann Modelsmentioning
confidence: 99%
“…Ramanathan et al, 2012;C. T. Ramanathan et al, 2011;) Pakistan 9 (Afzal et al, 2019;Akram et al, 2017;Choudhry et al, 2014Choudhry et al, , 2018Choudhry & Rehman Nasir, 2012;Hanif et al, 2016;Maqsoom et al, 2018;Samiullah Sohu et al, 2017;Zafar et al, 2016) China 6 (Afzal et al, 2019;Lou & Yin, 2010;Ma, 2011;Mansur et al, 2019;Wang & Yuan, 2011;Yuanyue & Huimin, 2018) Ghana 5 (Asiedu et al, 2017;Asiedu & Adaku, 2019;Coffie et al, 2019) Nigeria 4 (Akinradewo et al, 2019;Akinsiku et al, 2014;Amadi & Higham, 2019;Amusan et al, 2018;Hingham, 2016) Saudi Arabia 4 (Alghonamy, 2015;Mahamid, 2013Mahamid, , 2018Seddeeq et al, 2019) South Africa 4 (Khabisi, 2012;Monyane et al, 2018;Mulalo et al, 2018 (Jung et al, 2016;Kavuma et al, 2019;Qiao et al, 2019) Vietnam 3 (S. Kim et al, 2017;S. Y. Kim et al, 2018;Pham et al, 2020) Others 21 (Afzal et al, 2019;Al-hazim et al, 2017;Alzebdeh et al, 2015;Apolot & Tindiwensi, 2013;…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Samarghandi et al used regression techniques to quantify construction delay factors in Iran for residential projects and educational facilities [22]. Educational facilities have been a particular interest for assessing cost and time overruns, with a more advanced regression analysis executed by Asiedu et al [23]. Samarghandi et al used linear regression techniques where a single dependent variable was correlated with a single independent variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Asiedu et al team used multiple linear regression (MLR), where they identified 10 predictive variables that could influence cost overruns. The MLR analysis determined that five of the variables influenced the overruns [23]. A study of 911 building projects in Ghana also applied MLR analysis in the statistical software R and considered seven predictive variables [24].…”
Section: Literature Reviewmentioning
confidence: 99%